2021
DOI: 10.20338/bjmb.v15i1.236
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous and asynchronous remote exercise may improve motor and non-motor symptoms in people with Parkinson’s disease during the COVID-19 pandemic

Abstract: BACKGROUND: Stay active is a good strategy to mitigate the negative effects of confinement in people with Parkinson’s Disease (PD). Synchronous (full-time class interaction) and asynchronous (without the live presence of the healthcare professional) exercises are two strategies to avoid the worsening of PD. AIM: To investigate the effect of the synchronous and asynchronous exercise on motor and non-motor symptoms in people with PD during the pandemic lockdown. METHOD: Fifty-eight people with PD responded to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…For instance, in a recent Italian survey with 75 people with MS ( Motolese et al, 2020 ), the authors observed an increase in depressive symptoms, such as worse sleep quality, and higher fatigue symptoms during the lockdown. Similar results were observed for people with PD: individuals with a reduced amount of physical activity reported worsening of motor symptoms during the pandemic lockdown ( Schirinzi et al, 2020 ), while individuals with PD which are more active ( Santinelli et al, 2021 ). Also, longer periods without going out of the house could increase psychological stress, anxiety, and depression symptoms, consequently decreasing the quality of life and sleep quality ( Yalachkov et al, 2019 ; Prasad et al, 2020b ).…”
Section: Introductionsupporting
confidence: 73%
“…For instance, in a recent Italian survey with 75 people with MS ( Motolese et al, 2020 ), the authors observed an increase in depressive symptoms, such as worse sleep quality, and higher fatigue symptoms during the lockdown. Similar results were observed for people with PD: individuals with a reduced amount of physical activity reported worsening of motor symptoms during the pandemic lockdown ( Schirinzi et al, 2020 ), while individuals with PD which are more active ( Santinelli et al, 2021 ). Also, longer periods without going out of the house could increase psychological stress, anxiety, and depression symptoms, consequently decreasing the quality of life and sleep quality ( Yalachkov et al, 2019 ; Prasad et al, 2020b ).…”
Section: Introductionsupporting
confidence: 73%
“…Similarly, online fall prevention programs have been found to be feasible and acceptable to older participants [34,35], supporting the premise of a teleyoga program designed to prevent falls. Although there is currently limited evidence about the effects of online exercise programs that offer synchronous (real time) versus asynchronous (prerecorded) classes [36,37], some studies suggest that synchronous programs are more engaging with higher levels of adherence and physical activity [38][39][40].…”
Section: Introductionmentioning
confidence: 99%